Impact of dehulling, germination and fermentation on the bioactive and functional properties of grey pea flour - Amanipour, Armaghan; Samaei, Yasaman; Böök, Olof; Granfeldt, Yvonne; Lazarte, Claudia E. (Frontiers in Nutrition, 2024)
Introduction Grey pea is a largely overlooked legume in the Nordic countries, and its potential uses in various food products remain unexplored. It is a nutrient-rich crop with low environmental impact, making it an attractive option for sustainable and nutritious plant-based alternatives. Objectives To investigate the impact of dehulling, germination, and fermentation on the bioactive (polyphenol content and antioxidant capacity) and functional characteristics (water absorption index, water solubility index, water and oil binding capacity, emulsifying properties and gelation concentration) of grey pea flour. Additionally, protein content and pasting properties (temperature, peak viscosity, trough viscosity, breakdown, final viscosity, and setback) were measured. Methods Dehulling was performed using a runner disk sheller. Germination was carried out for 24 and 48 h at ambient temperature, and fermentation was conducted for 8 h at 43°C using a starter culture. Results The results indicate that dehulling did not significantly affect functional properties and gelling capacity (p = 0.297 for oil absorption capacity, p = 0.5 for emulsion activity, and p = 0.607 for emulsion stability), but it resulted in a notable decrease in total polyphenol content (TPC) and antioxidant capacity (TAC). Conversely, 48 h of germination increased TAC measured by two methods: FRAP (19%) and DPPH (30%). This process increased through viscosity by 1.2-fold, while it did not significantly affect the water absorption index (WAI), water solubility index (WSI), or the emulsifying properties of grey pea flour. Fermentation significantly improved TPC (p < 0.001 for whole grey peas and p = 0.004 for dehulled grey peas), with a TPC increase of up to 67% in fermented dehulled pea flour. TAC measured by both methods, showed significant increases, ranging from 35 to 104%. However, fermentation reduced emulsifying and pasting properties, as indicated by the peak, through and final viscosity, which may be desirable only for certain food products. Further, germination and fermentation showed significant increases in protein content, by 4 and 8%, respectively. Conclusion Fermented grey pea flour exhibited enhanced bioactive characteristics, while 48-h germination positively impacted pasting properties. Overall, these processes led to changes in both the bioactive and functional properties of grey pea flour, creating opportunities for the use of these flours in a wide array of food products.